Civil engineering systems analysis - Amador-Jimenez, Luis (CRC Press/Taylor & Francis, 2017)
This textbook covers tools and applications in civil engineering systems. It begins by revising the mathematical and statistical background for the adequate formulation of civil engineering problems. It covers problem definition, model formulation and decision making systems, including optimization, estimation and prediction.